KAZAKHSTANI FINANCIAL SECTOR PERFORMANCE FEATURES UNDER CURRENT CONDITIONS - Nurymova S.; Yessentay A.; Khalitova M.; Jumabayev Y.; Zainal M. (Scientific Journal of Pedagogy and Economics, 2019)
The financial sector is one of the most, if not the most significant economic sector in modern societies. In advanced countries, it employs more people than major manufacturing industries combined and accounts for a high percentage of the Gross Domestic Product. But the financial services sector also plays a large indirect role in national economies. The financial sector mobilizes savings and allocates credit across space and time, and enables firms and households to cope with uncertainties by hedging, pooling, sharing and pricing risks. This ultimately improves the quantity and quality of real investments and increases income per capita and raises standards of living. Today financial institutions are experiencing unprecedented change in a competitive global environment. The existing model of the financial system of Kazakhstan requires modernization in order to increase the possibilities to finance strategically important areas in the economy and society. In turn, the state should change its policy of active financing to the policy of active stimulation. The purpose of writing this article and making research was to justify a model of an investment and financial system with a financial center, capable for the formation of a knowledge-based economy and the creation of an infrastructure of intellectual modernization of society. We highlighted the existing conceptual approaches to the financial support of a knowledge-based economy and social and intellectual modernization of society in the article. The analysis of the banking and insurance sectors of the economy, the insurance market and the stock market was carried out, and the positive aspects and advantages of creating a financial center - AIFC were highlighted. In addition, the work revealed the peculiarities of the participation of the financial system of Kazakhstan in the development of knowledge-intensive sectors of the economy and the intellectual renewal of society, and also highlighted the factors and conditions for restarting the financial system of Kazakhstan and determining the model of investment and financial system. The world experience in the use of tools and methods for financing high-tech industries has been studied, which made it possible to determine the general principles for financing a knowledge-intensive economy.